Poloidal ULF wave observed in the plasmasphere boundary layer. Issue 7 (23rd July 2013) - Liu, W.; Cao, J. B.; Li, X.; Sarris, T. E.; Zong, Q.‐G.; Hartinger, M.; Takahashi, K.; Zhang, H.; Shi, Q. Q.; Angelopoulos, V.
Abstract: [1] We report on a rare ultra‐low‐frequency (ULF) wave generation event associated with the formation of a plasmasphere boundary layer (PBL), which was well observed by one of the THEMIS satellites, TH‐D, during subsequent outbound passes. On 13 September 2011, TH‐D observed a sharp plasmapause at L = 3.4. The plasmasphere started to expand and continued to be refilled on 14 September. On 15 September, a PBL was formed with two density gradients at L = 4.4 and 6.5, respectively. Within the two density gradients, strong radial magnetic field and azimuthal electric field oscillations were observed, suggesting poloidal ULF waves. Based on the phase delay between magnetic and electric field signals, as well as the comparison between the observed wave frequency and predicted harmonic eigenfrequency, we find that the observed oscillations are second harmonic poloidal waves. Further investigation shows that the observed waves are likely generated by drift‐bounce resonance with "bump‐on‐tail" plasma distributions at 10 keV. We demonstrate that the waves are excited within the PBL where the eigenfrequency is close to the bounce frequency of these hot protons, but not outside the PBL where the eigenfrequency deviates from the bounce frequency. Finally, we suggest that cold plasma density seems to be a controlling factor for ULF wave generation as well, in addition to the bump‐on‐tail energy source, by altering eigenfrequency of the local field lines. Key Points: A rare ULF wave event associated with the formation of a PBL is reported. The wave is second harmonic poloidal mode generated by drift bounce resonance. Cold plasma density plays an important role in regulating ULF wave generation.